Fievel goes west [videorecording (DVD)] - Nibbelink, Phil; Wells, Simon; Cavadini, Cathy; Stewart, James, 1908-1997; Cleese, John; Irving, Amy, 1953-; DeLuise, Dom (Universal Home Video, 2003)
The Mousekewitz family discovers the streets of America are not all paved with cheese, and living in a mouse tenement does not offer the life they hoped for. Young Tanya dreams of becoming a famous singer, and Fievel wants to become a tough lawdog like his hero Wylie Burp. Lured out west by the crafty entrepreneur Cat R. Waul, Fievel discovers the evil gentleman's true plans to turn the settlers into mouse-burgers. Enlisting the aid of his cat friend Tiger, the two team up with the legendary Wylie Burp to stop the feline gang's dastardly plot.